Quantifying water and energy linkages in irrigation experiences from Vietnam. (Metro Manila, Philippines Asian Development Bank, 2017)
This publication summarizes the results of a pilot study to quantify water and energy use in high-effciency irrigation systems in Vietnam.
Keywords: Agricultural resources -- Management -- Vietnam; Agriculture -- Economic aspects -- Vietnam; Electronic books